2021
DOI: 10.3390/cancers13164105
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Loss and Octogenarian Status Are Associated with S-1 Adjuvant Therapy Discontinuation and Poor Prognosis after Pancreatectomy

Abstract: The efficacy and prognosis of adjuvant chemotherapy for resected pancreatic cancer remain unclear. We investigated the utility and risk factors of S-1 adjuvant chemotherapy in patients with pancreatic cancer undergoing pancreatectomy. This study comprised 80 patients, including 58 patients who received S-1 adjuvant chemotherapy. Skeletal muscle loss was defined using cutoff values of skeletal muscle mass index. In total, 16 (20%) octogenarian patients underwent pancreatectomy. Skeletal muscle loss was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Among the 12 studies included, 1 was in the neo-adjuvant setting ( 31 ), 2 in the adjuvant setting ( 30 , 37 ), 3 in the metastatic setting ( 32 , 33 , 36 ); 2 in the unresectable setting ( 26 , 29 ); the other 4 included more than one clinical setting ( 22 , 34 , 35 , 38 ). Eight of the included studies were from Japan ( 22 , 26 , 29 32 , 34 , 35 ); 1 from South Korea ( 33 ); 1 from Canada ( 36 ); 1 from Brazil ( 37 ); 1 from Australia ( 38 ); all 12 studies were retrospective ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 12 studies included, 1 was in the neo-adjuvant setting ( 31 ), 2 in the adjuvant setting ( 30 , 37 ), 3 in the metastatic setting ( 32 , 33 , 36 ); 2 in the unresectable setting ( 26 , 29 ); the other 4 included more than one clinical setting ( 22 , 34 , 35 , 38 ). Eight of the included studies were from Japan ( 22 , 26 , 29 32 , 34 , 35 ); 1 from South Korea ( 33 ); 1 from Canada ( 36 ); 1 from Brazil ( 37 ); 1 from Australia ( 38 ); all 12 studies were retrospective ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the trials including gemcitabine, 2/9 demonstrated an association with toxicity, whereas 7/9 did not; among those including FOLFIRINOX, one demonstrated associated toxicity whereas the others did not. Altogether, 4/12 papers demonstrated an association between the body composition values and the development of chemotherapy-related toxicities (1 between low SMI and hematological toxicity and reduction of cycles number ( 29 ); 1 between loss of skeletal muscle and discontinuation of chemotherapy ( 30 ); 1 between low SMI and low SMD with all grade 3 toxicities ( 33 ); 1 with hematological toxicity ( 22 )). Associations of body composition values and chemo-related toxicities are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations